2021
DOI: 10.1136/bmjopen-2020-044685
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 has affected general practice consultations and income: general practitioner cross-sectional population survey evidence from Ireland

Abstract: ObjectivesHow general practice is delivered in many countries has drastically changed due to the COVID-19 pandemic. This study aimed to answer the question of how general practice has changed in Ireland in response to COVID-19.DesignThe Irish College of General Practitioners surveyed its membership before and after the global pandemic hit Ireland using a cross-sectional online survey instrument.SettingThis study focuses on primary care, specifically general practice, in Ireland.ParticipantsIn February 2020 bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 17 publications
1
47
1
Order By: Relevance
“…First, the COVID-19 crisis has negatively impacted the activity of general and specialized practices. For example, a survey of approximately 530 general practitioners from Ireland revealed that the number of face-to-face consultations went from 32,160 in February 2020 to 10,484 in June 2020 (Homeniuk and Collins 2021 ). Another study including 678 dermatologists surveyed between April and May 2020 showed that daily clinical activity had reduced by more than 75% during the pandemic for almost half of the sample, while approximately 40% of participants reported working fewer days per week compared with before the COVID-19 pandemic (Conforti et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the COVID-19 crisis has negatively impacted the activity of general and specialized practices. For example, a survey of approximately 530 general practitioners from Ireland revealed that the number of face-to-face consultations went from 32,160 in February 2020 to 10,484 in June 2020 (Homeniuk and Collins 2021 ). Another study including 678 dermatologists surveyed between April and May 2020 showed that daily clinical activity had reduced by more than 75% during the pandemic for almost half of the sample, while approximately 40% of participants reported working fewer days per week compared with before the COVID-19 pandemic (Conforti et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the data from this survey were collected during the peak of the pandemic in Italy, it is also likely that this number might be due to the difficulties in mobility experienced by citizens while the lockdown measures were being implemented, as well as the fear of being infected by the virus by visiting clinics and hospitals [ 27 ], even though telephone consultations were generally available at the time. However, this may also be symptomatic of a lack of patient trust in their primary doctor and of the perception of hindrances in the direct communication with him/her [ 28 , 29 ]. Doctor-patient communication has been largely demonstrated to be a crucial factor of sustaining patient engagement in self-management [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In There has been a significant increase in the use of telemedicine for GP and other healthcare consultations since the onset of the pandemic. Homeniuk and Collins (2021), for example, found that prior to the pandemic, 10.5 per cent of GP consultations in Ireland were telemedicine, compared to 57 per cent during the pandemic. It remains to be seen if telemedicine consultations will continue to be a significant feature of primary care as the COVID-19 pandemic and associated restrictions dissipate.…”
Section: Primary Care and The Covid-19 Pandemicmentioning
confidence: 99%